Analysis of Employee Performance Assessment the Office of Regional Development Planning Agency, Pangandaran, West Java, Indonesia - Andre Ariesmansyah; Abdul Rosid; Rifqi Khoerul Arifin (Formosa Journal of Multidisciplinary Research, 2023)
This study aims to determine the Employee Performance Assessment in Bappeda Pangandaran Regency. This type of research is descriptive research using a qualitative approach. The data collection technique used was interviews with informants who were considered to know the research problems. The results of this study show: first, from the dimension of work results where the implementation of the work given by each employee is quite good. Second, from the dimension of work skills from the indicators of responsibility the employees always complete their work on time, from the indicators of good cooperation it can be seen from the establishment of good cooperation between employees and creating conducive conditions. Third, from the dimension of work discipline, compliance with regulations is also quite good but there are some employees who still don't comply with the rules. Fourth, from the potential dimension, in increasing job duties there are still employees who have not been able to complete more difficult tasks. in complying with the rules is also quite good but there are some employees who still do not comply with the rules.